Micro-optofluidic lenses : a review - Nguyen, Nam-Trung (2012)
This review presents a systematic perspective on the development of micro-optofluidic lenses. The progress on the development of micro-optofluidic lenses are illustrated by example from recent literature. The advantage of micro-optofluidic lenses over solid lens systems is their tunability without the use of large actuators such as servo motors. Depending on the relative orientation of light path and the substrate surface, micro-optofluidic lenses can be categorized as in-plane or out-of-plane lenses. However, this review will focus on the tunability of the lenses and categorizes them according to the concept of tunability. Micro-optofluidic lenses can be either tuned by the liquid in use or by the shape of the lens. Micro-optofluidic lenses with tunable shape are categorized according to the actuation schemes. Typical parameters of micro-optofluidic lenses reported recently are compared and discussed. Finally, perspectives are given for future works in this field.